2009
DOI: 10.1073/pnas.0906471106
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet amyloidosis, β-cell apoptosis, and α-cell proliferation are determinants of islet remodeling in type-2 diabetic baboons

Abstract: ␤-Cell dysfunction is an important factor in the development of hyperglycemia of type-2 diabetes mellitus, and pancreatic islet amyloidosis (IA) has been postulated to be one of the main contributors to impaired insulin secretion. The aim of this study was to evaluate the correlation of IA with metabolic parameters and its effect on islets of Langerhans remodeling and relative endocrine-cell volume in baboons. We sequenced the amylin peptide, determined the fibrillogenic propensities, and evaluated pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 50 publications
(45 reference statements)
12
113
0
Order By: Relevance
“…Ageing was positively correlated with the severity of islet amyloidosis, and increased amyloidosis was associated with an increased rate of alpha cell replication and beta cell apoptosis [128].…”
Section: Old Agementioning
confidence: 95%
“…Ageing was positively correlated with the severity of islet amyloidosis, and increased amyloidosis was associated with an increased rate of alpha cell replication and beta cell apoptosis [128].…”
Section: Old Agementioning
confidence: 95%
“…More precise-ly, some investigators suggested the potential involvement of a-cells in b-cell regeneration after observing cells coexpressing glucagon and insulin in several pancreatic regeneration models. Another interesting observation is that diabetic patients have an increased a-cell mass [69,70]; similarly, a-cell proliferation was increased in STZ-treated rats, and a-cells expressed b-cell markers such as Pdx1, Glut2 (Slc2a2) and insulin [31,66,71]. In the same way, bcell ablation induced by DOX in Ins2-rtTA; TetO-DTA mice was followed by the appearance of a very small number of glucagon+/insulin+ bihormonal cells, although these cells were not lineage-traced and their contribution to the formation of new b-cells was not explored [50].…”
Section: Reprogramming Pancreatic Cells Into B-cellsmentioning
confidence: 99%
“…6C,D). Since dysregulation of amylin has been associated with β-cell death in type 2 diabetes (Huang et al 2007;Guardado-Mendoza et al 2009), it will be interesting to know in which cells and the exact portion of cells where amylin becomes dysregulated during diabetes onset.…”
Section: End Sequence Analysis Toolkit (Esat)mentioning
confidence: 99%